Inventarisasi Tumbuhan Obat Yang Dimanfaatkan Oleh Masyarakat Desa Durian Pandaan Kabupaten Pesisir Selatan - Novi; Vivi Septrilia (Biotropic : The Journal of Tropical Biology, 2020)
Utilization of natural plants as medicine is one of the skills that has been scarce found even some places only become a wisdom by the local community. The use of natural plants as traditional medicine by the Durian Pandaan villagers is still widely used for traditional medicine. Among the medicinal plants used, the scientific name of the plant is still unknown. The purpose of this study was to determine the types of medicinal plants used by the Durian village community. This study used a descriptive survey method with direct observation and field interviews with 3 herbalists. Samples that have been fielded can be directly photographed intact and identified. The results of research conducted in the village of Durian Pandaan obtained 77 species from 44 families. With the highest use value is Curcuma domestic